GENERATION OF A RECOMBINANT Α-AMYLASE, AMY1UA7, FROM BACILLUS SUBTILIS IN ESCHERICHIA COLI - Kalimkulova , M.; Kiribayeva , A.; Mukhamedyarov , D.; Kulametov , Zh.; Akhmetollayev , I.; Silayev , D.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2015)
Enzymes that mediate hydrolysis of starch-containing raw materials are widely used in the modern biotechnology industry. In the present study, a recombinant α-amylase, Amy1UA7, from Bacillus subtilis was generated in Escherichia coli, in order to study its biochemical parameters. The Amy1UA7 gene was synthesized by oligonucleotides and cloned in a pET-28c (+) vector under the control of the bacteriophage T7 promoter. Recombinant Amy1UA7 was obtained in BL21 (DE3) cells by plasmid gene expression; protein purification was carried out by metal affinity chromatography. During the study, the temperature and acid optimum of the recombinant enzyme was fixed, and the impact of metal ions and organic acids on enzymatic activity was determined. Analysis of the effect of temperature on the activity of Amy1UA7 demonstrated that the efficiency of starch hydrolysis by the recombinant α-amylase increased up to + 50°C to + 55°C, when amylase activity had a maximum value of 165 U. The results also demonstrated that amylase α-Amy1UA7 remains active in a wide pH range (4–9) while retaining more than 80% of its maximum activity. In addition, it is a calcium-independent enzyme that has tolerance to a range of metal ions and organic acids. These data are essential for encouraging the use of recombinant enzymes in biotechnological processes involving the hydrolysis of polysaccharides.